Evaluation of morphological and functional changes in placental villi and trophoblast cells in response to Plasmodium falciparum infection (2024)
This study investigated the impact of Plasmodium falciparum-infected erythrocytes (P. falciparum-iE) on placental tissue through three complementary models: an in vitro model with BeWo cells, an ex vivo model with human placental explants (HPEs), and an in vivo exposition that incorporated tissues from naturally infected pregnant individuals. Qualitative, semiquantitative, and quantitative analyses were conducted in each model to assess the potential physiopathological effects of placental malaria. Each process was detailed extensively in the methodology specific to its objectives. In the in vitro model, an increase in cellular damage was observed, evidenced by the elevation of LDH activity in cells exposed to P. falciparum-iE compared to control cells. Additionally, there was a decrease in hCG hormone production and an impairment in the cellular differentiation process, especially in citotrofoblast cells exposed to P. falciparum-iE, which exhibited inadequate cellular fusion, as reflected in the analysis of E-cadherin expression. This phenomenon was accompanied by a decrease in the expression of key mediators for syncytialization, such as SYN-1, SYN-2, and hCG. In the ex vivo model, a decrease in cellular viability and alterations in placental tissue integrity were observed, including damage to the trophoblast membrane, disorganization of collagen in the villous stroma, and a decrease in the distribution of Collagen I and III. Additionally, areas of thickening of the basal lamina were detected, coinciding with regions of trophoblast detachment and rupture. Furthermore, elevated levels of inflammatory mediators, primarily IL-6 and IL-10, were found in HPEs exposed to P. falciparum-iE compared to control HPEs. The evaluated angiogenic mediators did not show significant differences between exposed HPEs and the control. In the in vivo study, significant changes were identified in villous stromal damage, with a reduction in the organization of collagen fibers similar to what was found ex vivo. The trophoblast membrane remained intact in the tissues, and no regions of thickening in the basal lamina were observed, differentiating it from the ex vivo model. These findings could be related to the exposure time and maternal healing and immune response processes that might be involved in the in vivo model but not in the ex vivo model. It is essential to note that each finding should be interpreted according to the characteristics of the specific model, considering the potential effects of the exposure time to infection on the evaluated cells and tissue. Overall, these results suggest that the interaction of P. falciparum-iE with cytotrophoblast and placental villi may disrupt the integrity, function, and profile of factors produced and released by these cells and tissues, contributing to the dysregulation of various processes in the maternal-fetal interface.